he use of types of feedback and its impact on the acquisition of learning and retention of some basic skills in five-a-side football, an experimental study on a sample of football school players at Al-Shoula Sports Club for ages (12-14 years). (Journal of the College of Basic Education, 2022)
The research aims to.Using types of feedback in acquiring learning some basic skills in five-a-side ballfoot.- To know the effect of using different types of feedback on learning acquisition and retention.Some basic skills in five-a-side football and their development rates.The research included the use of the experimental method, and the sample consisted of two players from the football school of the ClubAthlete torch The sample was distributed into two experimental groups and also included tests and methodsstatistical.It also included the presentation and analysis of the results of the pre and post tests for the two experimental groups.and discuss it.The research reached the following conclusions:The first experimental group that used the feedback (additional, video CD)image and sound) has achieved significant results indicating its superiority over the second experimental group inHandling skills and targeting.The research recommends:The necessity of adopting the feedback within the training curriculum and giving it the appropriate space.- Emphasis on the use of feedback as an effective method in the learning process.